Floristic Assessment of the Peruvian North Coast Pastures - Tovar, Oscar (2005)
This paper describes 84 species of the Peruvian north coast pastures, from Tumbes – Trujillo (3º30’ – 8º S). Savannas are predominant vegetation type in the area, where algarrobo Prosopis pallida is the dominant tree and the pastures are basically Poaceae (grasses) over a large area. Keys for taxonomic identification of families, genera and species are included, and commentaries on geographical distribution.